Hersey and Blanchard's Situational Leadership Model as an Effort to Improve School Achievement - Mukhtar, Mukhtar; Soedjono, Soedjono; Kusumanigsih, Widya (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
The aims of the study are to analyse and describe the role of Hersey and Blanchard’s situational leadership model, namely directing, coaching, supporting, and delegating, in improving school achievement. This study uses a qualitative approach with a phenomenological method. The location of the study is at SD Muhammadiyah 01, Comal Subdistrict, Pemalang Regency. Data was obtained from primary and secondary sources involving the principal and three teachers. Data collection was conducted through in-depth interviews, participatory observation, and documentation studies. Data analysis used Miles and Huberman's interactive analysis model, which consists of data collection, data condensation, data display, and conclusion drawing/verification. Data validity was ensured through technique triangulation, source triangulation, and time triangulation. The findings indicate that the directing style did not play a role in improving school achievement, while the coaching, supporting, and delegating styles played a significant and strategic role in improving school achievement, and the principal was more dominant in applying the delegating style in improving school achievement at SD Muhammadiyah 01 Comal Subdistrict.